2014
DOI: 10.1021/ie5036572
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dissolved Metals and Oxidative Degradation Inhibitors on the Oxidative and Thermal Degradation of Monoethanolamine in Postcombustion CO2 Capture

Abstract: In the present work, the influence of metal ions and oxidative degradation inhibitors on the stability of monoethanolamine solvents (MEA) is studied. 2 induces additional costs and impacts the environmental balance of the CO 2 capture process as well as its efficiency. The two main degradation pathways of MEA are studied under accelerated conditions: oxidative degradation with continuous gas feed and thermal degradation in batch reactors. It is confirmed that metal ions (resulting from solvent impurities and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…Use of chemical additives to cut down degradation can also help reduce work load of the solvent purification process. Various degradation inhibitors have been proposed over the past years (Idem et al, 2009b;Saxton and Rochelle, 2009;Lee et al, 2013;Leonard et al, 2014). Therefore, the capture process using different amines can pick and choose inhibitors appropriate for the solvents.…”
Section: Solvent Cleaning Degradation Prevention Recycling and Reclmentioning
confidence: 99%
“…Use of chemical additives to cut down degradation can also help reduce work load of the solvent purification process. Various degradation inhibitors have been proposed over the past years (Idem et al, 2009b;Saxton and Rochelle, 2009;Lee et al, 2013;Leonard et al, 2014). Therefore, the capture process using different amines can pick and choose inhibitors appropriate for the solvents.…”
Section: Solvent Cleaning Degradation Prevention Recycling and Reclmentioning
confidence: 99%
“…Other improvements would be to consider flue gas contaminants like SO x and NO x , to include the effect of degradation on solvent performances, and to consider degradation reactions inside additional process blocs (e.g., Voice (2013) has shown that oxidative degradation also significantly occurs in the cross heat exchanger). Similarly, the influence of degradation inhibitors as studied in Léonard et al (2014d) should also be modeled if such inhibitors are used to prevent MEA oxidative degradation.…”
Section: Resultsmentioning
confidence: 99%
“…Heavy metals, like iron, chromium, nickel, and manganese may get into the amine solution from equipment and pipes made from stainless steel, however, copper and vanadium may be added to amine solvents as components of corrosion inhibitors [13].…”
Section: Introductionmentioning
confidence: 99%